THE DIFFERENCE BETWEEN NEWLY DISCOVERED CIRCUMSTANCES AND OTHER STAGES OF CIVIL PROCEEDINGS - Akhmedova Feruza Akhmedovna (European Science Publishing, 2024)
The author analyzes the stage of review of a civil case based on newly discovered circumstances, revealing the general and distinctive features of its implementation in comparison with other types of review of a civil case according to the legislation of the Republic of Uzbekistan. The article is also devoted to the analysis of approaches to the doctrinal definition of the concept of newly discovered circumstances in civil proceedings. The author proposes to give a legislative definition to the concept of reviewing judicial acts based on newly discovered circumstances.
Keywords: newly discovered circumstances, new circumstances, circumstances essential to the case, special circumstances, grounds for revision, appeal revision, cassation, revision proceedings, legal facts, application, civil proceedings, stage, revision of judicial acts, revision procedure.